(untitled) (Proceedings of Southern Federal University. Philology, 2018)
Marzhanat N. Nabigulaeva (Makhachkala, Republic of Dagestan, Russian Federation) The article deals with the analysis of moral and ethical traditions in the works of Avar poets of different epochs: Abubakar from Aimaki, Ali-Gadzhi from Inkho and Gamzat Tsadasa, who made a significant contribution to the formation and development of this direction, revealed the origin of their traditions, ways of their existence and continuity in national poetry. They all – Abubakar from Aimaki, Ali-Haji from Inkho and Gamzat Tsadasa – were versatile educated, enlightened people of their time, they were precisely aware of the slightest downturns in the moral foundations in society and fought for them, propagandized, asserted their importance and value. Each of them, in accordance with the requirements, actual moral and ethical issues of contemporary reality, made a contribution to the development of this direction in Avar literature. The main motives for their creativity were the faith in the Almighty, the trend to knowledge and diligence, to life based on the eternal behavioral values of morality and ethics. With moral and ethical traditions, education and work they directly linked harmony in people’s lives, their well-being, and Gamzat Tsadasa more broadly – the overall development of the country and its future. He has a special merit in this, since the moral and didactic direction forms the basis of his poetry which was of great importance in the struggle with the vestiges of the past, the foundations of the old way of life, and played an important role in eliminating blood feuds in the mountains, emancipating mountain women, disseminating education etc. Key words: sources, development, traditions, religious motives, morals, ethics and morality, instruction, enlightenment, work. DOI 10.23683/1995-0640-2018-1-21-30